Greenhouse production of baby leaf vegetables using rainbow trout wastewater in a high-tech vertical decoupled aquaponic system - Chatzigeorgiou, Ioanna; Ravani, Maria; Papadopoulos, Dimitrios K.; Kelesidis, George; Giantsis, Ioannis A.; Tsaballa, Aphrodite; Koukounaras, Athanasios; Ntinas, Georgios K. (Frontiers in Horticulture, 2024)
Introduction Aquaponics is an integrated food production system that links recirculating aquaculture with hydroponics, leading to higher water use efficiency than conventional food production systems while also saving on fertilizers. In the present study, baby lettuce and baby rocket plants cultivated hydroponically in a deep water culture system using wastewater from rainbow trout were evaluated as part of a vertical decoupled aquaponic system. Materials and methods More specifically, three different nutrient solutions were supplied: a) using fish wastewater only (designated as Fish); b) fish wastewater enriched with synthetic fertilizers (Mix); and c) a typical nutrient solution (Hoagland) as the control. Both lettuce and rocket plants were monitored in these nutrient solutions and in two different substrates, peat and perlite, as an organic and an inert substrate, respectively. The purpose of this study was to assess a vertical decoupled aquaponic system with regard to the resource use efficiency, such as water, land, and energy, while evaluating plant cultivation in the different treatments in terms of yield, growth, nitrate concentration on the leaf tissue, and foliar analysis. The photosynthetic rate and leaf color indices were also considered in the plant evaluation. Results The Mix–Peat treatment was the most efficient growing combination in terms of land and water use efficiency, with approximately 7% better land use efficiency while using 38% less water and 10% less fertilizer than Hoagland–Peat. Moreover, lettuce plants had the highest yield in the Mix–Peat treatment, at 2,497 g m−2, which was approximately 6% higher than that of Hoagland–Peat while not being inferior in the quality measures. On the other hand, the yield of rocket was significantly higher in the Hoagland–Peat treatment, being 18% higher than that of Mix–Peat and 30% higher than that of Fish–Peat. Overall, the study confirmed that aquaponic systems could lead to higher water use efficiency and savings in fertilizers without undermining the yield and quality of lettuce, while the vertical arrangement developed within the scope of this study can increase the land useefficiency of the system.